Refugee women's well-being, needs and challenges: implications for health policymakers - BARIŞ, HATİCE EZGİ; BORAN, PERRAN (OXFORD UNIV PRESS, 2020)
Background Refugees face circumstances where their health and well-being are compromised. In this qualitative study, the aim was to understand Syrian refugee women's needs for care and the predisposing and enabling factors to healthcare access and utilisation. Methods Out of 945 Syrian mothers who gave birth in our university hospital between 2014 and 2018, 195 were reached; out of which, 47 women were included. Semi-structured in-depth interviews were conducted and were later analysed using a qualitative content analysis approach. Depression was assessed by the Patient Health Questionnaire-9 at the end of the interview. Results Social isolation and maternal depression, language barrier and challenges while navigating the healthcare system emerged as the main themes of the study. Low educational and occupational status of the women, poor social resources, limited Turkish proficiency and unfamiliarity with the host healthcare system were identified as the predisposing factors for poor healthcare services utilisation. Conclusion Recommendations include bridging language gaps, improving the navigation of the healthcare system by visual support or in-person interpretation, and psychosocial support. Providing hospital-based language courses to mothers and social integration programs for families will improve the mothers' well-being and indirectly care of the child.
Keywords: health services; mental health; refugees; women's health; POSTPARTUM DEPRESSION; EXPERIENCES; IMMIGRANT; RESETTLEMENT; PREVALENCE